APPLICATION OF THE ANTIBACTERIAL AND ANTIFUNGAL MEDICATIONS IN THE EXTERNAL THERAPY OF THE CHILDREN WITH ATOPIC DERMATITIS OF VARIOUS SEVERITY AGGRAVATED BY THE SECONDARY INFECTION - N.G. Korotkiy; A.A. Tikhomirov; B.N. Gamayunov (Union of pediatricians of Russia, 2007)
The article deals with the research findings of the clinical efficiency and tolerance of the combined medication gentamaicin + betamethasone + clotrimazole (triderm, scheringaplough, usa) in the external therapy of atopic dermatitis of various severity aggravated by the secondary skin infection. The researchers monitored 40 children aged between 2 and 17 years old. The evaluation of the disease severity and therapy efficiency was performed with the aid of the scorad coefficient. The monitoring period made up 3 weeks. The research findings showed that after the monitoring period elapsed, the clinical remission of atopic dermatitis was observed among 20 patients, while 19 patients had a considerable improvement of the state, whereas 1 patient had an imporvement of his status. no side effects were registered. Thus, the research findingds allow one to recommend the wide application of the medication in the children's dermatoa logic practice.Key words: atopic dermatitis, children, treatment, gentamicin + betamethasone + clotrimazole.